2017
DOI: 10.21032/jhis.2017.42.2.162
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Self-leadership in the Relationship between Career Decision Level and Career Preparation Behavior of Nursing Students

Abstract: The purpose of this study was to investigate the mediating effect of self-leadership on the relationship between career decision level and career preparation behavior of nursing students. Methods: The subjects were 179 nursing college students using questionnaires with a total of 63 items including general characteristics (11 items), career decision level (18 items), career preparation (16 items), and self-leadership (18 items) respectively. The collected data were analyzed by SPSS Statistics 23 using the mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
1
0
0
1
Order By: Relevance
“…It can be said that nursing students enter the professional world in a situation where the profession of nursing is predetermined upon entering the nursing department, and they lack in-depth consideration of their career preparation. A study reported that the more nursing students believe that their career path is predetermined, the higher their employment stress, so it is necessary to provide specific career education and counseling during university life and strengthen career preparation behaviors for nursing students' successful employment and adaptation to various fields after graduation [10]. In this study, it was confirmed that career decision self-efficacy and self-leadership were improved after applying the calligraphy program.…”
Section: Discussionsupporting
confidence: 62%
“…It can be said that nursing students enter the professional world in a situation where the profession of nursing is predetermined upon entering the nursing department, and they lack in-depth consideration of their career preparation. A study reported that the more nursing students believe that their career path is predetermined, the higher their employment stress, so it is necessary to provide specific career education and counseling during university life and strengthen career preparation behaviors for nursing students' successful employment and adaptation to various fields after graduation [10]. In this study, it was confirmed that career decision self-efficacy and self-leadership were improved after applying the calligraphy program.…”
Section: Discussionsupporting
confidence: 62%
“…과정에 나타나는 진로에 대한 확고한 정도를 의미하며 [6] [15,16], 진로결정 수준의 영향요인으 로 우울, 주관적 건강 등의 심리적 요인 [17,18], 진로결정 자기효능감 [1,19], 진로의사결정 유형 [11] 및 진로탐색행동 [13]…”
unclassified